Combined treatment for the control of arterial hypertension about a case - Dra. Mayra Sánchez (2010)
Hypertension affects one in four adults woridwide. The control of blood pressure isessential for reducing cardiovascular events. Pharmacotherapy for hypertension mayreduce this risk significantiy. However, the control of hypertension in the communityis farfrom optimal.The literature presents a wide range of factors influencing compliance or failure ofmedical treatment, involving components of psychosocial, medical and doctor-patient relationship. The OMS highiighted the influence of socioeconomic factors andthose related to the system or equipment that provides health services may also influence the fact pathologies added, and the use of more medicines, plus the durationof treatment. Failure to take necessary measures to comply with the control of bloodpressure, increase the complications and risk factors for developing cardiovasculardisease